The association between CGRP gene -624 T→C polymorphism and headache severity in Turkish migraine patients (Annals of Medical Research, 2024)
Aim: This study aims to explore -624 T→C polymorphism on CGRP gene in migraine patients, and the relation between this polymorphism and migraine attacks.Materials and Methods: The study registered a total of 101 migraine patients, 17 with aura and 84 without aura and 80 healthy volunteers. CGRP -624 T→C polymorphism in migraine patients and the control group was evaluated using PCR-RFLP method.Results: Although no significant difference could be found between genotype and allele frequencies of CGRP -624T→C polymorphism in the patient and control groups (p>0.05). In addition, a statistically significant positive correlation was established between the severity of headache and C allele of this gene in migraine patients (p
Keywords: Migraine; CGRP; Gene polymorphism